2018
DOI: 10.1111/ene.13552
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and nerve conduction features in Guillain−Barré syndrome associated with Zika virus infection in Cúcuta, Colombia

Abstract: Guillain-Barré syndrome associated with ZIKV infection in Cúcuta is characterized by a high frequency of cranial nerve involvement, autonomic dysfunction and requirement of mechanical ventilation indicating an aggressive and severe course. AIDP is the most frequent electrophysiological subtype. Demyelination is prevalent distally but this pattern is not specific for ZIKV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Traveller/non-traveller populations: In studies included in this update, we found additional evidence of GBS in both travellers and non-travellers with ZIKV infection. Ten publications report on 11 travellers 218, 220, 222224, 227, 229, 232– 234 , while 34 publications report GBS due to ZIKV in 402 non travellers 4, 44, 118, 219, 221, 225, 226, 228, 230, 231, 235– 237, 239– 247, 249, 251, 253260, 262, 263 .…”
Section: Resultsmentioning
confidence: 99%
“…Traveller/non-traveller populations: In studies included in this update, we found additional evidence of GBS in both travellers and non-travellers with ZIKV infection. Ten publications report on 11 travellers 218, 220, 222224, 227, 229, 232– 234 , while 34 publications report GBS due to ZIKV in 402 non travellers 4, 44, 118, 219, 221, 225, 226, 228, 230, 231, 235– 237, 239– 247, 249, 251, 253260, 262, 263 .…”
Section: Resultsmentioning
confidence: 99%
“… 29 Infectious agents thought to cause parainfectious neuropathies include Borrelia burgdorferi , Brucella , Clostridium botulinum and West Nile virus. 30 More recently, infection with the flavivirus Zika has been associated with the development of both postinfectious and parainfectious GBS. 14 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CNS glia are highly susceptible in vitro, consistent with white matter pathology in pre-term and newborn infants with congenital Zika virus infection (Chimelli et al, 2017 ). Whether Zika-GBS has an autoimmune etiology (Uncini et al, 2017 ) or is due to a direct viral neuropathogenic mechanism remains to be determined.…”
Section: General Pathology and Mechanisms Of Axonal Injurymentioning
confidence: 99%